A THEORETICAL APPROACH TO LINGUISTIC POWER (JOURNAL OF ANCIENT HISTORY AND ARCHAEOLOGY, 2024)
In the 1st century BC, Cilicia faced a complex political landscape with the declining authority of the Seleucid Empire. The arrival of the Romans in the region led to a significant change, bringing increased political stability and the suppression of piracy. However, Cilicia’s transformation into a Roman province was a gradual process, and it was characterized by significant changes, particularly in terms of language. Local languages coexisted with Greek until Greek gained prominence. Even then, local cults persisted in certain settlements. Remarkably, the Roman presence did not immediately alter the linguistic landscape, as no Latin inscriptions dating before the Sullan period have been found in Cilicia. This suggests that Greek remained the primary language in daily life during the early Roman period. Furthermore, archaeological evidence indicates that Latin was primarily used in administrative contexts, such as milestones, as Cilicia transitioned into a Roman province. This linguistic diversity provides a unique perspective on the region’s cultural amalgamation. Hence, this article presents a theoretical framework for understanding the linguistic changes driven by Roman influence, by shedding light also on their political and social implications to assess how effectively the local population embraced these changes. Through an analysis of Latin integration in both administrative and everyday contexts, it aims to gain insight into its power.